Biodiesel production process from microalgae oil by waste heat recovery and process integration. (October 2015) - Song, Chunfeng; Chen, Guanyi; Ji, Na; Liu, Qingling; Kansha, Yasuki; Tsutsumi, Atsushi
Graphical abstract: Highlights: Novel biodiesel production process from microalgae oil was exploited. Exergy recovery and heat integration was applied to save energy consumption. Energy requirement of the optimized process was reduced to 0.592 /L biodiesel. Operational cost decreased by 22.5% and 41.6% compared to the reference cases. Abstract: In this work, the optimization of microalgae oil (MO) based biodiesel production process is carried out by waste heat recovery and process integration. The exergy analysis of each heat exchanger presented an efficient heat coupling between hot and cold streams, thus minimizing the total exergy destruction. Simulation results showed that the unit production cost of optimized process is 0.592 /L biodiesel, and approximately 0.172 /L biodiesel can be avoided by heat integration. Although the capital cost of the optimized biodiesel production process increased 32.5% and 23.5% compared to the reference cases, the operational cost can be reduced by approximately 22.5% and 41.6%.